From Entertainment to Education: The Transformation of Social Media in the Promotion of Adolescent Mental Health - Qurniyawati, Eny; Fauziyah Masse, Nur (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Teens undergo significant physical, emotional, and social changes that increase their vulnerability to mental health issues. I-NAMHS reports that one in three adolescents aged 10–17 experience mental health problems. Despite efforts, reaching and engaging adolescents remains challenging. Edutainment offers an innovative approach to promoting adolescent mental health. However, its effectiveness and application across digital platforms are still limited and require further research. Objective: This study aims to analyze research trends on edutainment as a tool for education and mental health promotion among adolescents. Methods: Using bibliometric analysis, we mapped research trends related to edutainment in mental health promotion. Data were collected from Google Scholar, Scopus, and PubMed, then analyzed with VOSviewer. Results: Analyzing 141 articles published between 2019 and 2021, we observed a significant increase in research on edutainment and mental health. Seven main clusters emerged, with social media (Instagram, Twitter, Facebook) being the largest, followed by film, music, and K-pop culture. Mental health apps and video games are more specific but less prominent topics. Conclusion: Social media dominates edutainment research for mental health promotion, with film and music also prominent. Video games and mental health apps have a smaller scope but remain relevant. Overall, edutainment continues to grow as an effective approach, with social media playing a key role in recent trends.